Beyond national markets: The case of emerging African multinationals. Issue 2 (3rd May 2020) - Esho, Ebes; Verhoef, Grietjie
ABSTRACT: Findings from research on emerging market multinationals (EMNEs) have posed some intriguing questions to scholars. While some of the questions are easy to explain through the lens of extant theories, others are more complex. Research on African multinationals is limited and being only a recent phenomenon, historical accounts of their internationalization is scarce. Early findings suggest that African firms exhibit distinct internationalization behaviour from other EMNEs. However, are EMNEs from Africa and their internationalization behaviour unique? This paper expounds the internationalization of three nascent African multinationals through the lens of extant theories and finds that multiple theories converge to explain their internationalization. Their distinct paths to internationalization come from their independent efforts in navigating Africa's diverse, and sometimes extreme, contextual challenges and opportunities. Alongside the global orientation of founders that originates from their education and experience, relationships from founders' networks also play a dominant role in the internationalization process of African EMNEs. The conditions for business, especially for internationalization, in Africa are unique, and sometimes extreme. Institutional voids and informal markets, for example, are pervasive and huge. However, the African context enables a nuanced understanding of extant theories and the linkages between theories in explaining internationalization of EMNEs.